Degradation liquid for degrading unsaturated polyester type wind turbine blade and degradation and recovery method
Through the combination of polar solvents, alcohol solvents and organic alkalis, the problems of excessive catalyst use and high irritation of solvents in the prior art are solved, and the efficient and environmentally friendly degradation of unsaturated polyester wind blades are achieved. Fast speed and does not damage the equipment.
Patent Information
- Application Number
- CN202310710909.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-17
AI Technical Summary
The method of degrading unsaturated polyester resin materials in the prior art has the problems of excessive catalyst use, high solvent irritation, high reaction process pressure and insufficient environmental protection, resulting in the risk of insufficient environmental protection of degradation process and equipment damage.
The degradation solution is formed by mixing polar solvents, alcohol solvents and organic alkalis, and degrading is carried out by heating. The organic alkali is used as a catalyst. The degradation rate is fast and the amount is used is small. The degradation solution can be recycled and reused, and the degradation process is mild.
It achieves efficient degradation of unsaturated polyester wind power blades, the degradation solution has low corrosion, does not damage the equipment, and can recover a variety of polymer materials. The degradation process is simple and the process is environmentally friendly.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermosetting resin degradation and resource utilization, and specifically relates to a degradation liquid for degrading unsaturated polyester wind turbine blades and a degradation recovery method. Background Art
[0002] Unsaturated polyester resin has excellent chemical corrosion resistance, electrical properties and mechanical properties, so it is widely used in industry, agriculture and construction. Due to the large-scale use of unsaturated polyester resin, as well as the aging and discarding of scraps and industrial products generated during the production and processing, unsaturated polyester resin waste is increasing, most of which are buried on the spot or burned in the natural environment, causing great pollution to the environment. Especially in the field of wind turbine blade materials, the discarding of wind turbine blades (composed of unsaturated polyester resin and fiber) containing unsaturated polyester resin not only causes environmental pollution, but also these wastes are not well recycled. Therefore, how to deal with and recycle these unsaturated polyester resins and their composite materials has become a hot topic of research.
[0003] At present, a variety of methods for degrading and recovering unsaturated polyester resin materials are disclosed in the prior art. For example, Chinese patent application document CN104326907A discloses a method for degrading and recovering unsaturated polyester resin materials, which specifically uses chlorides, sulfates, nitrates or acetates of zinc ions, aluminum ions, etc. as catalysts, and acetic acid or acetic acid aqueous solution as a degradation system composed of a reaction solvent. The system can degrade unsaturated polyester materials under heating conditions and recover related products. However, in this scheme, more catalysts need to be added, resulting in strong corrosion of the degradation liquid, the solvent contains a large amount of acetic acid, which is highly irritating, the solvent has a low boiling point, the reaction process pressure is relatively high, and the degradation process is not environmentally friendly.
[0004] Chinese patent application document CN110590534 A discloses a method for selectively catalytically degrading and recovering unsaturated polyester resin waste. Specifically, the method uses a degradation system composed of a reaction solvent and an organic acid catalyst to selectively degrade unsaturated polyester waste. The method can degrade unsaturated polyester waste under heating conditions and recover related products. However, the scheme requires the use of a large amount of acetic acid or a low-boiling point solvent as a reaction solvent. Acetic acid is highly irritating, and low-boiling point solvents have a large vapor pressure at high temperatures. The reaction process has high requirements on equipment, and the degradation process is not environmentally friendly. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a degradation liquid for degrading unsaturated polyester wind turbine blades and a degradation recovery method. The degradation liquid of the present invention has the advantages of fast degradation speed and relatively small amount, and the degradation liquid can be recycled and reused, and can recycle a variety of high molecular substances; the degradation process is relatively mild.
[0006] One object of the present invention is to provide a degradation liquid for degrading unsaturated polyester wind turbine blades.
[0007] The degradation liquid comprises a polar solvent, an alcohol solvent and an organic base; wherein the mass proportion of the alcohol solvent relative to the total mass of the polar solvent and the alcohol solvent is 1% to 40%, preferably 3% to 30%; the mass proportion of the organic base relative to the total mass of the polar solvent and the alcohol solvent is 0.5% to 15%, preferably 1% to 10%.
[0008] In some embodiments, the polar solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylformamide.
[0009] In some embodiments, the alcohol solvent is a high-boiling point alcohol solvent; in some preferred embodiments, the high-boiling point alcohol solvent is selected from one or more of ethylene glycol, propylene glycol, benzyl alcohol, and polyethylene glycol 200.
[0010] In some embodiments, the organic base is a guanidine compound. In some preferred embodiments, the guanidine compound is selected from one or more of 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, and 1,5-diazabicyclo[4.3.0]non-5-ene.
[0011] Another object of the present invention is to provide a method for degrading and recycling unsaturated polyester wind turbine blades.
[0012] The degradation recovery method comprises the following steps:
[0013] S1. Mixing a polar solvent and an alcohol solvent uniformly to form a mixed solution, wherein the alcohol solvent accounts for 1% to 40% by weight of the mixed solution, preferably 3% to 30% by weight; adding an organic base to the mixed solution to form a degradation solution, wherein the organic base accounts for 0.5% to 15% by weight of the mixed solution, preferably 1% to 10% by weight;
[0014] S2, adding the unsaturated polyester wind turbine blade into the degradation liquid, and heating to 180-230° C. to degrade for 60-240 min;
[0015] S3. After the degradation is completed, the recovered fiber and liquid product are obtained by filtration. The liquid product is precipitated by adding water to obtain a degradation product containing styrene. The filtrate is distilled under reduced pressure to obtain an alcohol solvent for recovery and use.
[0016] In some embodiments, in step S1, the polar solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylformamide.
[0017] In some embodiments, in step S1, the alcohol solvent is a high-boiling point alcohol solvent; in some preferred embodiments, the high-boiling point alcohol solvent is selected from one or more of ethylene glycol, propylene glycol, benzyl alcohol, and polyethylene glycol 200.
[0018] In some embodiments, in step S1, the organic base is a guanidine compound. In some preferred embodiments, the guanidine compound is selected from one or more of 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, and 1,5-diazabicyclo[4.3.0]non-5-ene.
[0019] In some embodiments, in step S2, the mass proportion of the unsaturated polyester wind turbine blade relative to the degradation liquid is 10% to 40%, preferably 15% to 40%; in some preferred embodiments, in step S2, the heating degradation is carried out in a pressure-resistant closed reactor.
[0020] In some embodiments, in step S3, the solid product is washed and dried with alcohol, and then subjected to heat treatment to obtain a fiber material for reuse; preferably, the conditions for the heat treatment are 530-570°C, 1-3h; the degradation product is recycled after drying; the conditions for the reduced pressure distillation are 150-170°C, -0.15--0.05MPa; and the alcohol solvent is recycled.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention mixes polar solvents, alcohol solvents and organic bases to form a degradation liquid. The three cooperate with each other to greatly improve the degradation rate. The organic base is used as a catalyst, which has low corrosiveness and will not damage the equipment. The amount used is small. The degradation liquid can be recycled and reused, and a variety of high-molecular substances can be recycled. The degradation process is relatively mild and will not damage the performance of the recycled fiber. In addition, when the degradation liquid is used for the degradation and recovery of unsaturated polyester wind turbine blades, the degradation can be completed in a one-step method, and the process is simple. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.
[0025] The degradation rate test method of the unsaturated polyester wind turbine blade in the present invention is as follows:
[0026] Degradation rate of unsaturated polyester wind turbine blades = (blade mass before degradation - solid product mass after degradation) / (blade mass before degradation - fiber mass) × 100%,
[0027] The quality of the solid product after degradation: the degradation liquid after the degradation of the leaf material is filtered, the solid product obtained after filtration is washed with alcohol, and then placed in a vacuum drying oven at 150°C for 24 hours and weighed;
[0028] Fiber quality: The degraded solid product was heated in a muffle furnace at 550°C for 2 hours to remove the residual undegraded resin, and then weighed.
[0029] Example 1
[0030] After 36g of N-methylpyrrolidone and 4g of ethylene glycol are mixed evenly, 1.20g of 1,5,7-triazidobicyclo (4.4.0) dec-5-ene (TBD) is added and stirred for 30min to dissolve to form a degradation liquid, which is added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades are added to the degradation liquid, cut to a size of about (30mm*30mm*5mm), and weigh 7.641g, and heated to 220°C for degradation reaction for 120min. After the reaction is completed, solid products and liquid products can be obtained by filtration. The mass of the solid product after washing and drying with alcohol is 4.175g. After heating treatment, glass fiber is obtained for reuse. The liquid product is precipitated and filtered by adding 400ml of water. The filter cake is a degradation product containing styrene, which can be recycled after drying. The filtrate can be distilled at 160°C and -0.10MPa under reduced pressure to obtain a degradation product component containing alcohol substances, and water and solvent are recycled. The weight of the recycled glass fiber is 4.175 g, and the calculated degradation rate of the unsaturated polyester block is 100.0%.
[0031] Example 2
[0032] After 28g N,N-dimethylformamide and 12g propylene glycol are mixed evenly, 2.40g 1,5,7-triazidobicyclo (4.4.0) dec-5-ene (TBD) is added and stirred for 30min to dissolve to form a degradation liquid, which is added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades are added to the degradation liquid, cut to a size of about (30mm*30mm*5mm), and weigh 7.622g, and heated to 220℃ for degradation reaction for 180min. After the reaction is completed, solid products and liquid products can be obtained by filtration. The mass of the solid product after washing and drying with alcohol is 4.512g. After heating treatment, glass fiber is obtained for reuse. The liquid product is precipitated and filtered by adding 400ml water. The filter cake is a degradation product containing styrene, which can be recycled after drying. The filtrate can be distilled at 160℃ and -0.10MPa under reduced pressure to obtain a degradation product component containing alcohol substances, and water and solvent are recycled. The weight of the recycled glass fiber is 4.341 g, and the calculated degradation rate of the unsaturated polyester block is 94.8%.
[0033] Example 3
[0034] After 38.8g of dimethyl sulfoxide and 1.20g of benzyl alcohol are mixed evenly, 2.0g of 1,5,7-triazidobicyclo (4.4.0) dec-5-ene (TBD) is added and stirred for 30min to dissolve to form a degradation solution, which is added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades are added to the degradation solution, cut to a size of about (30mm*30mm*5mm), weighing 7.805g, and heated to 230°C for degradation reaction for 60min. After the reaction is completed, solid products and liquid products can be obtained by filtration. The mass of the solid product after washing and drying with alcohol is 4.997g. After heating treatment, glass fiber is obtained for reuse. The liquid product is precipitated and filtered by adding 400ml of water. The filter cake is a degradation product containing styrene, which can be recycled after drying. The filtrate can be distilled at 160°C and -0.10MPa under reduced pressure to obtain a degradation component containing alcohol substances, and water and solvent are recycled. The weight of the recycled glass fiber is 4.650 g, and the calculated degradation rate of the unsaturated polyester block is 89.0%.
[0035] Example 4
[0036] After 32g of N-methylpyrrolidone and 8g of benzyl alcohol are mixed evenly, 4.0g of 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD) is added and stirred for 30min to dissolve to form a degradation liquid, which is added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades are added to the degradation liquid, cut to a size of about (30mm*30mm*5mm), and weigh 7.686g, and heated to 200℃ for degradation reaction for 240min. After the reaction is completed, solid products and liquid products can be obtained by filtration. The mass of the solid product after washing and drying with alcohol is 4.536g. Then, after heating treatment, glass fiber is obtained for reuse. The liquid product is precipitated and filtered by adding 400ml of water. The filter cake is a degradation product containing styrene, which can be recycled after drying. The filtrate can be distilled at 160℃ and -0.10MPa under reduced pressure to obtain a degradation product component containing alcohol substances, and water and solvent are recycled. The weight of the recycled glass fiber is 4.370 g, and the calculated degradation rate of the unsaturated polyester block is 95.0%.
[0037] Example 5
[0038] After 30g of N-methylpyrrolidone and 10g of polyethylene glycol 200 are mixed evenly, 3.2g of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) is added and stirred for 30min to dissolve to form a degradation liquid, which is added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades are added to the degradation liquid, cut to a size of about (30mm*30mm*5mm), and weigh 7.901g, and heated to 200℃ for degradation reaction for 240min. After the reaction is completed, solid products and liquid products can be obtained by filtration. The mass of the solid product after washing and drying with alcohol is 5.141g. After heating treatment, glass fiber is obtained for reuse. The liquid product is precipitated and filtered by adding 400ml of water. The filter cake is a degradation product containing styrene, which can be recycled after drying. The filtrate can be distilled at 160℃ and -0.10MPa under reduced pressure to obtain a degradation product component containing alcohol substances, and the water and solvent are recycled. The weight of the recycled glass fiber is 4.754 g, and the calculated degradation rate of the unsaturated polyester block is 87.7%.
[0039] Example 6
[0040] After 36g of N-methylpyrrolidone and 4g of ethylene glycol are mixed evenly, 1.60g of 1,5,7-triazidobicyclo (4.4.0) dec-5-ene (TBD) is added and stirred for 30min to dissolve to form a degradation solution, which is added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades are added to the degradation solution, cut to a size of about (30mm*30mm*5mm), and weigh 7.713g, and heated to 180°C for degradation reaction for 120min. After the reaction is completed, solid products and liquid products can be obtained by filtration. The mass of the solid product after washing and drying with alcohol is 5.388g. After heating treatment, glass fiber is obtained for reuse. The liquid product is precipitated and filtered by adding 400ml of water. The filter cake is a degradation product containing styrene, which can be recycled after drying. The filtrate can be distilled at 160°C and -0.10MPa under reduced pressure to obtain a degradation product component containing alcohol substances, and water and solvent are recycled. The weight of the recycled glass fiber is 4.860 g, and the calculated degradation rate of the unsaturated polyester block is 81.5%.
[0041] Example 7
[0042] After 36g N,N-dimethylacetamide and 4g ethylene glycol are mixed evenly, 2.80g 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) is added and stirred for 30min to dissolve to form a degradation liquid, which is added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades are added to the degradation liquid, cut to a size of about (30mm*30mm*5mm), and weigh 7.755g, and heated to 210℃ for degradation reaction for 180min. After the reaction is completed, solid products and liquid products can be obtained by filtration. The mass of the solid product after washing and drying with alcohol is 4.464g. After heating treatment, glass fiber is obtained for reuse. The liquid product is precipitated and filtered by adding 400ml water. The filter cake is a degradation product containing styrene, which can be recycled after drying. The filtrate can be distilled at 160℃ and -0.10MPa under reduced pressure to obtain a degradation product component containing alcohol substances, and the water and solvent are recycled. The weight of the recycled glass fiber is 4.352 g, and the calculated degradation rate of the unsaturated polyester block is 96.7%.
[0043] Example 8
[0044] After 36g of N-methylpyrrolidone and 4g of ethylene glycol are evenly mixed, 3.60g of 1,5,7-triazidobicyclo (4.4.0) dec-5-ene (TBD) is added and stirred for 30min to dissolve to form a degradation liquid, which is added into a pressure-resistant closed reactor. Unsaturated polyester wind turbine blades are added into the degradation liquid, cut into a size of approximately (30mm*30mm*5mm), and 2 cut blades are added, with a total weight of 15.521g. The temperature is raised to 220°C for degradation reaction for 240min. After the reaction is completed, solid products and liquid products can be obtained by filtering. The mass of the solid product after washing and drying with alcohol is 10.898g. Then, after heating treatment, glass fiber is obtained for reuse. The liquid product is precipitated and filtered by adding 400ml of water. The filter cake is a degradation product containing styrene, which can be recycled after drying. The filtrate can be obtained by decompression distillation at 160°C and -0.10MPa to obtain a degradation product component containing alcohol substances, and water and solvent are recycled. The weight of the recycled glass fiber is: 9.813g, and the degradation rate of the unsaturated polyester block is calculated to be: 81.0%.
[0045] Comparative Example 1
[0046] 36g of N-methylpyrrolidone and 4g of ethylene glycol were mixed evenly to form a degradation solution, which was added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades were added to the degradation solution, cut to a size of about (30mm*30mm*5mm), weighing 7.561g, and heated to 220°C for degradation reaction for 120min. A solid product and recovered glass fiber were obtained in the same manner as in the example. After weighing, the solid product was 7.408g, the weight of the recovered glass fiber was 6.835g, and the calculated degradation rate of the unsaturated polyester block was 21.1%.
[0047] Comparative Example 2
[0048] After 20g of N-methylpyrrolidone and 20g of ethylene glycol are mixed evenly, 1.20g of 1,5,7-triazidobicyclo (4.4.0) dec-5-ene (TBD) is added and stirred for 30min to dissolve to form a degradation solution, which is added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades are added to the degradation solution, cut to a size of about (30mm*30mm*5mm), weighing 7.542g, and heated to 220°C for degradation reaction for 120min. A solid product and recovered glass fiber are obtained in the same manner as in the embodiment. After weighing, the solid product is 6.362g, the weight of the recovered glass fiber is: 5.532g, and the calculated degradation rate of the unsaturated polyester block is: 58.7%.
[0049] Comparative Example 3
[0050] After 36g of N-methylpyrrolidone and 4g of ethylene glycol were mixed evenly, 1.20g of 1,5,7-triazidobicyclo (4.4.0) dec-5-ene (TBD) was added and stirred for 30min to dissolve to form a degradation solution, which was added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades were added to the degradation solution, cut to a size of about (30mm*30mm*5mm), weighing 7.678g, and heated to 160°C for degradation reaction for 120min. A solid product and recovered glass fiber were obtained in the same manner as in the embodiment. After weighing, the solid product was 6.824g, the weight of the recovered glass fiber was: 5.952g, and the calculated degradation rate of the unsaturated polyester block was: 49.5%.
[0051] Comparative Example 4
[0052] After 36g of N-methylpyrrolidone and 4g of ethylene glycol were mixed evenly, 3.60g of 1,5,7-triazidobicyclo (4.4.0) dec-5-ene (TBD) was added and stirred for 30min to dissolve to form a degradation solution, which was added to a pressure-resistant closed reactor, and unsaturated polyester wind turbine blades were added to the degradation solution, cut to a size of about (30mm*30mm*5mm), and 3 pieces of cut blades were added, with a total weight of 22.685g, and the temperature was raised to 220°C for degradation reaction for 240min. A solid product and recovered glass fiber were obtained in the same manner as in the embodiment. After weighing, the solid product was 18.556g, the weight of the recovered glass fiber was: 16.162g, and the calculated degradation rate of the unsaturated polyester block was: 63.3%.
[0053] Comparison between Comparative Example 1 and Example 1 shows that without adding a catalyst to the degradation solution, the degradation efficiency is significantly reduced under the same conditions;
[0054] Comparison between Comparative Example 2 and Example 1 shows that when the alcohol solvent added to the degradation solution exceeds the proportion, the degradation efficiency is significantly reduced under the same conditions;
[0055] Comparison between Comparative Example 3 and Example 1 shows that when the temperature of the degradation solution is lower than 180°C, the degradation efficiency is significantly reduced under the same degradation conditions;
[0056] Comparison between Comparative Example 4 and Example 8 shows that when the total amount of waste leaves added is too large, the degradation liquid cannot fully contact the leaves, the degradation reaction process is hindered, and the degradation efficiency is significantly reduced under the same degradation conditions.
[0057] The above embodiments are only specific implementation methods of the present invention, which are used to illustrate the technical solutions of the present invention rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the aforementioned embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the protection scope of the present invention.
Claims
1. A degradation liquid for degrading unsaturated polyester wind turbine blades, characterized in that: The degradation liquid comprises a polar solvent, an alcohol solvent and an organic base; wherein the mass proportion of the alcohol solvent relative to the total mass of the polar solvent and the alcohol solvent is 1% to 40%, preferably 3% to 30%; the mass proportion of the organic base relative to the total mass of the polar solvent and the alcohol solvent is 0.5% to 15%, preferably 1% to 10%.
2. The degradation liquid for degrading unsaturated polyester wind turbine blades according to claim 1, characterized in that: The polar solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylformamide.
3. The degradation liquid for degrading unsaturated polyester wind turbine blades according to claim 1, characterized in that: The alcohol solvent is a high-boiling point alcohol solvent; preferably, the high-boiling point alcohol solvent is selected from one or more of ethylene glycol, propylene glycol, benzyl alcohol, and polyethylene glycol 200.
4. The degradation liquid for degrading unsaturated polyester wind turbine blades according to claim 1, characterized in that: The organic base is a guanidine compound. Preferably, the guanidine compound is selected from one or more of 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, and 1,5-diazabicyclo[4.3.0]non-5-ene.
5. A method for degrading and recycling unsaturated polyester wind turbine blades, characterized in that: The steps include: S1. Mixing a polar solvent and an alcohol solvent uniformly to form a mixed solution, wherein the alcohol solvent accounts for 1% to 40% by weight of the mixed solution, preferably 3% to 30% by weight; adding an organic base to the mixed solution to form a degradation solution, wherein the organic base accounts for 0.5% to 15% by weight of the mixed solution, preferably 1% to 10% by weight; S2, adding the unsaturated polyester wind turbine blade into the degradation liquid, and heating to 180-230° C. to degrade for 60-240 min; S3. After the degradation is completed, a solid product and a liquid product are obtained by filtration. The liquid product is precipitated by adding water to obtain a degradation product containing styrene. The filtrate is subjected to reduced pressure distillation to obtain an alcohol solvent for recovery and use.
6. The method for degrading and recycling unsaturated polyester wind turbine blades according to claim 5, characterized in that: In step S1, the polar solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylformamide.
7. The method for degrading and recycling unsaturated polyester wind turbine blades according to claim 5, characterized in that: In step S1, the alcohol solvent is a high-boiling point alcohol solvent; preferably, the high-boiling point alcohol solvent is selected from one or more of ethylene glycol, propylene glycol, benzyl alcohol, and polyethylene glycol 200.
8. The method for degrading and recycling unsaturated polyester wind turbine blades according to claim 5, characterized in that: In step S1, the organic base is a guanidine compound. Preferably, the guanidine compound is selected from one or more of 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, and 1,5-diazabicyclo[4.3.0]non-5-ene.
9. The method for degrading and recycling unsaturated polyester wind turbine blades according to claim 5, characterized in that: In step S2, the mass proportion of the unsaturated polyester wind turbine blade relative to the degradation liquid is 10% to 40%, preferably 15% to 40%.
10. The method for degrading and recycling unsaturated polyester wind turbine blades according to claim 5, characterized in that: In step S3, the solid product is washed and dried with alcohol, and then subjected to heat treatment to obtain a fiber material for reuse; preferably, the conditions for the heat treatment are 530-570°C, 1-3h; the degradation product is recycled after drying; the conditions for the reduced pressure distillation are 150-170°C, -0.15--0.05MPa; and the alcohol solvent is recycled.
Citation Information
Cited By
Degradable epoxy resin system material and application thereof, body, composite material and recovery method thereof
CN119570199A
Method for degrading polyester plastics under mild conditions
CN120987749A
